A Mobile Health Solution Complementing Psychopharmacology-Supported Smoking Cessation: Randomized Controlled Trial - Carrasco-Hernández, Laura; Jódar-Sánchez, Francisco; Núñez-Benjumea, Francisco; Moreno Conde, Jesús; Mesa González, Marco; Civit-Balcells, Antón; Hors-Fraile, Santiago; Parra-Calderón, Carlos L.; Bamidis, Panagiotis D.; Ortega Ruiz, Francisco (JMIR PUBLICATIONS, INC, 2020)
Objective: This study aimed to analyze the long-term efficacy of a mobile app supporting psychopharmacological therapy for smoking cessation and complementarily assess the involved innovative technology. Methods: A 12-month, randomized, open-label, parallel-group trial comparing smoking cessation rates was performed at Virgen del Rocío University Hospital in Seville (Spain). Smokers were randomly allocated to a control group (CG) receiving usual care (psychopharmacological treatment, n=120) or an intervention group (IG) receiving psychopharmacological treatment and using a mobile app providing artificial intelligence-generated and tailored smoking cessation support messages (n=120). The secondary objectives were to analyze health-related quality of life and monitor healthy lifestyle and physical exercise habits. Safety was assessed according to the presence of adverse events related to the pharmacological therapy. Per-protocol and intention-to-treat analyses were performed. Incomplete data and multinomial regression analyses were performed to assess the variables influencing participant cessation probability. Results: In the IG, abstinence was 2.75 times higher (adjusted OR 3.45, p=0.01) in the per-protocol analysis and 2.15 times higher (adjusted OR 3.13, p=0.002) in the intention-to-treat analysis. Lost data analysis and multinomial logistic models showed different patterns in participants who dropped out. Regarding safety, 14 of 120 (11.7%) IG participants and 13 of 120 (10.8%) CG participants had 19 and 23 adverse events, respectively (p=0.84). None of the clinical secondary objective measures showed relevant differences between the groups. Conclusions: The proposed mHealth solution complementing psychopharmacological therapy showed greater efficacy for achieving 1-year tobacco abstinence as compared with psychopharmacological therapy alone.
Keywords: Tabaquismo - Tratamiento; Cesación tabáquica; Cambio de comportamiento; MHealth